Histamine N-methyltransferase Modulates Human Bronchial Smooth Muscle Contraction - J. Tamaoki; A. Chiyotani; E. Tagaya; K. Isono; K. Konno (Mediators of Inflammation)
To elucidate the modulatory role of histamine-degrading enzymes in airway constrictor responses, human bronchial strips were studied under isometric conditions in vitro. Pretreatment of tissues with the histamine N-methyltransferase (HMT) inhibitor SKF 91488 specifically potentiated the contractile responses to histamine, causing a leftward displacement of the concentration response curves, whereas the diamine oxidase inhibitor aminoguanidine had no effect. This potentiation was attenuated by mechanical removal of the epithelium. The HMT activity was detected in the human bronchi, which was less in the epithelium-denuded tissues than the epithelium-intact tissues. These results suggest that HMT localized to the airway epithelium may play a protective role against histamine-mediated bronchoconstriction in humans.